A Cost-Effectiveness Analysis of an Adjuvanted Subunit Vaccine for the Prevention of Herpes Zoster and Post-Herpetic Neuralgia. (4th October 2017) - Carpenter, Christopher; Aljassem, Annas; Stassinopoulos, Jerry; Pisacreta, Giovanni; Hutton, David
Abstract: Background: Herpes zoster (HZ) develops in up to 50% of unvaccinated individuals who live to 85 years of age, accounting for more than 1 million cases of HZ annually in the United States. A live attenuated vaccine (LAV) for HZ is U.S. FDA approved for persons 50 years or older, though CDC Advisory Committee on Immunization Practices (ACIP) recommendations are only for persons beginning at age 60 years. LAV efficacy at preventing HZ is 70% for persons 50–59 years of age, with lower efficacy in older adults, and it is efficacious in preventing post-herpetic neuralgia (PHN) beyond the HZ prevention. The efficacy of LAV after vaccination wanes over time. A new adjuvanted HZ subunit vaccine (SUV), administered as a two-dose series, has greater than 95% efficacy against HZ in persons 50–69 years of age. SUV efficacy remains greater than 90% in persons vaccinated at age 70 years and older, including the subgroup older than 80 years of age. Overall efficacy of SUV against PHN approaches 90%. The waning rate of efficacy after SUV vaccination is unknown. Methods: To estimate the relative cost-effectiveness of SUV, LAV and no vaccination (NV) strategies, a Markov model was developed based on published trials and data on vaccine efficacy persistence, quality of life, resource utilization, costs and disease epidemiology. The perspective was U.S. societal, and the cycle length was one year with a lifelong time horizon. SUV efficacy was estimated for the base case to wane at the same rate as LAV, all persons were assumed to receive both doses of SUV, and the cost of SUV included both doses. Results: For individuals vaccinated at age 50 years the incremental cost-effectiveness ratio (ICER) for LAV vs. NV was 142, 811 per quality-adjusted life-year (QALY); at age 60 years the ICER dropped to 59, 482 per QALY. The cost-effectiveness ratio of SUV approached that of LAV when the SUV cost approached 500 for persons vaccinated at age 50 years and when the cost was 400 for those vaccinated at age 60 years. The SUV cost that would result in achieving an ICER target of 100, 000 per QALY for SUV vaccination vs. NV at age 50 years was 316; at age 60 years the cost was 638. Conclusion: Vaccination at age 60 years with SUV was more cost-effective than LAV when SUV cost was 450 or less. Vaccination with SUV at age 50 years appeared to be cost-effective if SUV cost was 315 or less. Disclosures: All authors: No reported disclosures.